Implementing hamstring injury prevention programmes remotely: a randomised proof of concept trial - Nicol van Dyk; Fearghal P Behan; Enda Francis Whyte; Lance Rane; Emma Thorne; Alexa Banaghan; Kevin Gilsenan (BMJ Open Sport & Exercise Medicine, 2024)
Objectives This study aimed to (1) compare the effectiveness of a Nordic hamstring exercise (NHE) versus single-leg Romanian deadlift (SLRDL) exercise programme on a hamstring injury risk surrogate; (2) compare the muscle soreness experienced by both exercise programmes; and (3) assess compliance to remote injury prevention exercise protocols through video software.Methods Twenty participants (10 women and 10 men: 21.45±1.6 years; 176±23 cm; 70±10 kg) were randomised into an NHE or SLRDL programme for 6 weeks. Single-leg hamstring bridge (SLHB), a hamstring injury surrogate, was the primary outcome for exercise efficacy. Muscle soreness and exercise adherence were also assessed. Significance was set at p<0.05.Results Both exercises increased SLHB performance resulting in an overall effect (p=0.013) with no effect for group (p=0.470) and no interaction effect (p=0.709), indicating both groups improved but there was no difference in improvement between interventions. There was no difference in muscle soreness between groups (p=0.087). Finally, both groups had 100% adherence to the programme.Conclusions Both the NHE and SLRDL are equally effective in increasing SLHB performance and demonstrate a similar level of muscle soreness. This suggests that SLRDL may be a viable option as a preventative exercise to mitigate the risk of hamstring injury. Finally, implementing injury prevention programmes remotely has the potential to enhance adherence.